A compact frequency reconfigurable hybrid DRA for LTE/Wimax applications - Aqeel, Sajid; Kamarudin, Muhammad Ramlee; Khan, Aftab Ahmad; Saleem, Jawad; Nasir, Jamal; Kazim, Jalil-ur-Rehman; Owais, Owais (Hindawi Publishing, 2017)
A compact hybrid antenna structure with frequency reconfiguration capabilities is presented in this article. The proposed design employs a combination of a rectangular DR element and a coupling slot on the structure’s ground plane (GP). The slot shifts the fundamental DRA mode by introducing a slow wave effect and its resonant behavior helps to achieve an omni-directional pattern at low frequencies. The slot is loaded with a series of PIN diode switches whose ON/OFF combinations alter the effective slot length. Slot loading with PIN diodes results in frequency reconfiguration of the proposed structure with a large tuning range of 76.2 % (between 1.73 to 3.86 GHz). A parametric analysis was performed to investigate the effects of slot length, width and position on the reflection coefficients of the proposed structure. A prototype of the proposed design was fabricated and results were measured. The measured results show a close agreement with the simulated ones. The proposed design is suitable for DCS 1800 MHz, PCS 1900 MHZ, UMTS, LTE 2500-2700 MHz, and Wimax 3.5 GHz.